Epimeria rafaeli sp. nov. (Crustacea, Amphipoda, Epimeriidae) from Western Australia - Coleman, Charles Oliver; Lowry, James K. (Zootaxa, 2014)
Members of the family Epimeriidae are reported in Australian waters for the first time and Epimeria rafaeli sp. nov. is described from deep water just south of the Abrolhos Island, Western Australia.